Building momentum for local action on problem gambling in Leeds and Yorkshire. (July 2020) - Elbers, M.; Rowlands, J.; Boo, M.; Cameron, I.
Abstract: Problem gambling has not been a priority within either Leeds City Council or partnership plans. However, financial inclusion, licencing and public health teams have been able to develop a cross-Council approach to problem gambling. This has been aided by an upfront payment plus annual payments to the Council that have been part of the licencing agreement for a new casino. As a result, research has been commissioned on local prevalence. This showed a higher rate of problem gamblers (1.8%) than national estimates with a similar level to nationally of those 'at risk'. The research also showed that local services had difficulties identifying problem gamblers and signposting for support. This had led to a high profile communications campaign to coincide with 'Responsible Gambling Week' complemented by training for frontline workers. The interviews undertaken for the research, plus the findings themselves, have been a powerful help in securing interest and commitment beyond the Council and to the health and third sectors. The use of local stories has helped build momentum for partnership working. For example, focus groups to explore how gambling affected migrants and medical student interviews with university students. The article will describe how increasing understanding across partners has helped build confidence to provide cross city responses to national consultations and contribute to national publications and conferences. Of even greater significance, the local National Health Service has secured funding from GambleAware for a Northern Gambling Service to be based in Leeds with satellites in the North East and Greater Manchester. This will provide treatment for those with severe gambling addiction. Additional support will come from a significant increased provision of GamCare services working to identify, screen and support problem gamblers. The use of Council premises for both of these services is testament to joint working. Recognising that this is a new emerging agenda has led to the creation of a Yorkshire and Humber Problem Gambling Working Group, endorsed by the Association of Directors of Public Health. This has resulted in shared learning and determining a consistent approach to harm. Even during a short time, the degree of interest has risen substantially. A regional gambling harm reduction framework has been produced that sets out a menu of actions. This intends to help local areas determine their own priorities. There is increasing recognition that problem gambling is a public health issue. Leadership requires a systems led, and Health in All Policies, approach to ensure problem gambling is not seen as a narrow niche issue led by public health staff. There is a need to recognise that engagement takes time. However, this is a new and emerging issue. The solutions to problem gambling are not clear and this allows for more creative, pragmatic and coproduced approaches. Highlights: Leeds research revealed problem gambling prevalence of twice the national average. Solutions are not clear, which allows for pragmatic and coproduced approaches. Partnerships have enabled a new treatment offer in Leeds and the north of England. A regional framework was developed with practical actions for local authorities.